2019
DOI: 10.1152/ajplung.00391.2018
|View full text |Cite|
|
Sign up to set email alerts
|

Prophylactic treatment with MSC-derived exosomes attenuates traumatic acute lung injury in rats

Abstract: The mesenchymal stem cell (MSC) is a potential strategy in the pretreatment of traumatic acute lung injury (ALI), a disease that causes inflammation and oxidative stress. This study aimed to investigate whether MSC-exosomal microRNA-124-3p (miR-124-3p) affects traumatic ALI. Initially, a traumatic ALI rat model was established using the weight-drop method. Then, exosomes were obtained from MSCs of Sprague-Dawley rats, which were injected into the traumatic ALI rats. We found that miR-124-3p was abundantly-expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 51 publications
1
61
0
Order By: Relevance
“…MSCs have been a potential strategy in the pretreatment of pulmonary diseases and MSCs-CM may be a preferable therapeutic option for ALI [37]. MiR-124-3p transferred by MSCs-derived exosomes had been demonstrated to inhibit purinergic receptor P2X ligand-gated ion channel 7P2X7 expression, thus improving oxidative stress injury and suppressing inflammatory response in traumatic ALI [38,39]. In our experiment, we focused on miR-124-5p and found the inhibition of miR-124-5p on α-ENaC by binding the 3′-UTR.…”
Section: Discussionmentioning
confidence: 99%
“…MSCs have been a potential strategy in the pretreatment of pulmonary diseases and MSCs-CM may be a preferable therapeutic option for ALI [37]. MiR-124-3p transferred by MSCs-derived exosomes had been demonstrated to inhibit purinergic receptor P2X ligand-gated ion channel 7P2X7 expression, thus improving oxidative stress injury and suppressing inflammatory response in traumatic ALI [38,39]. In our experiment, we focused on miR-124-5p and found the inhibition of miR-124-5p on α-ENaC by binding the 3′-UTR.…”
Section: Discussionmentioning
confidence: 99%
“…The other two studies investigated the functions of the MSC-EV contents. One study showed that EV trafficking of miR-124-3p directly targeted purinergic receptor P2X ligand-gated ion channel 7 to exert anti-inflammatory effects to protect the lungs in a trauma-induced acute lung injury (ALI) model 63 .…”
Section: Msc-evs In Respiratory Diseasesmentioning
confidence: 99%
“…Prophylactic treatment with mesenchymal stromal cell extracellular vesicles increased survival in rats undergoing traumatic lung injury; inflammatory cytokines, infiltrating leukocytes, and pulmonary edema were all reduced [34]. These effects were in part due to mesenchymal stromal cell extracellular vesicle transfer of miR-124 [34]. In a pig model of influenza-induced lung injury, administration of mesenchymal stromal cell extracellular vesicles similarly reduced lung injury, alveolar protein permeability, and inflammatory cytokine release.…”
Section: Benefits Of Extracellular Vesicles Derived From Mesenchymal mentioning
confidence: 92%
“…Mesenchymal stromal cell-derived extracellular vesicles isolated from conditioned media attenuated inflammation and lung injury in both intratracheal-LPS and E. coli pneumonia models of murine lung injury [32,33]. Prophylactic treatment with mesenchymal stromal cell extracellular vesicles increased survival in rats undergoing traumatic lung injury; inflammatory cytokines, infiltrating leukocytes, and pulmonary edema were all reduced [34]. These effects were in part due to mesenchymal stromal cell extracellular vesicle transfer of miR-124 [34].…”
Section: Benefits Of Extracellular Vesicles Derived From Mesenchymal mentioning
confidence: 98%